Bacille Calmette-Guérin adenitis: diagnostic and therapeutic guidelines. - Constant, Carolina; Figueiredo, António; Brito, Maria João (Acta Médica Portuguesa, 2011)
Bacille Calmette-Guérin (BCG) vaccination is occasionally associated with lymphadenitis, called BCGitis, and only rarely can it occur in the setting of immunodeficiency. We report six cases of BCGitis admitted to our hospital (2005-7) for surgical treatment: five were male, in all cases BCG was given at birth; median age at presentation was 5.5 months. Three children had spontaneous drainage, and one child had two lymph node regions involved (axillary and supraclavicular). Five required surgical drainage due to suppuration or persistence of lymphadenopathy. The patient with multiple lymph node involvement was treated with antimycobacterial therapy for suspected primary immunodeficiency, which was never confirmed. Immune function studies were normal in all cases. Average follow-up was 15 months. The therapeutical approach of suppurative lymphadenitis and the decision to investigate an underlying immunodeficiency is not consensual. We think that in the absence of disseminated disease an expectant attitude should be adopted.